Menggali Potensi Pengembangan Literasi Membaca di Sekolah Indonesia Bangkok (SIB) - Titik Mulyaningsih; Neni Mariana; Ari Metalin Ika Puspita (Journal on Education, 2024)
This research aims to explore the potential for developing reading literacy at Sekolah Indonesia Bangkok (SIB). Reading literacy is a critical aspect in the intellectual development of students and is a key factor for academic success. In the context of SIB, this research explores the challenges and opportunities faced by the school in enhancing reading literacy, as well as strategies that can be implemented to improve students' reading skills. The research methodology involves classroom observations, interviews with teachers and school staff, and analysis of documents related to literacy curriculum. The findings of this research identify several hindering factors to reading literacy at SIB, such as limited resources, lack of awareness of the importance of reading literacy, and language challenges for non-native students. Survey data indicates that the reading literacy of students at Sekolah Indonesia Bangkok is 82%, which is considered good, while the reading literacy of students at Sekolah Indonesia Bangkok is 92%, indicating it is very good. However, the research also reveals the potential for developing reading literacy through the implementation of innovative teaching methods, parental involvement, and collaboration with librarians or literacy specialists. Strategic recommendations are also proposed to support SIB's efforts in improving reading literacy, including the development of an integrated literacy curriculum and training for teachers. The results of this research are expected to provide a positive contribution to SIB and the education community in Thailand, as well as to serve as a guide for Indonesian schools abroad in optimizing their reading literacy programs.